Oxygen degradation in mesoporous Al2O3/CH3NH3PbI3-xClx perovskite solar cells: kinetics and mechanisms - Pearson, Andrew; Eperon, Giles E.; Hopkinson, Paul E.; Habisreutinger, Severin N.; Wang, Jacob Tse-Wei; Snaith, Henry J.; Greenham, Neil C. (Advanced energy materials, 2016)
The rapid pace of development for hybrid perovskite photovoltaics has recently resulted in promising figures of merit being obtained with regard to device stability. Rather than relying upon expensive barrier materials, realizing market-competitive lifetimes is likely to require the development of intrinsically stable devices, and to this end accelerated aging tests can help identify degradation mechanisms that arise over the long term. Here, oxygen-induced degradation of archetypal perovskite solar cells under operation is observed, even in dry conditions. With prolonged aging, this process ultimately drives decomposition of the perovskite. It is deduced that this is related to charge build-up in the perovskite layer, and it is shown that by efficiently extracting charge this degradation can be mitigated. The results confirm the importance of high charge-extraction efficiency in maximizing the tolerance of perovskite solar cells to oxygen.